The Phenomena of Using Instagram as an Educational Communication Tool Among University Students in Bandung - Nofha Rina; Reni Nuraeni (Communicatus: Jurnal Ilmu komunikasi, 2025)
This study aims to explore students’ motives, communication experiences, and behavioral changes in Instagram use as an educational communication medium. It employs a qualitative method with Alfred Schutz’s phenomenological approach, which emphasizes the subjective meaning of social action based on the structure of action motives: because motives and in-order-to motives. Data were collected through in-depth interviews and observations involving 20 university students in Bandung City who actively used Instagram for educational purposes. Data analysis was conducted through Schutz’s phenomenological stages combined with Braun and Clarke’s thematic analysis, including open coding, subtheme categorization, and the reflective and iterative construction of meaning-based themes. The findings indicated that Instagram use is shaped by ‘because motives’ rooted in prior academic experiences, such as difficulties in understanding classroom materials and a preference for visual content, and ‘in-order-to motives’ oriented toward future goals, including sharing educational values, building continuous learning, and promoting social change. The study also identified positive communication experiences through intersubjectivity and collaborative learning, alongside negative experiences that stimulate self-reflection, emotional literacy, and adaptation to digital communication ethics. Theoretically, this study extends the application of Schutz’s phenomenology within the field of digital educational communication. Practically, it strengthens digital literacy and optimizes Instagram as a meaningful learning space in higher education.